Sektorowe syntetyczne mierniki rozwoju w analizach papierów wartościowych - Łuniewska, Małgorzata (A Sector Synthetic Measures of Development in Securities Analysis, 2005)
In the paper is presented another approach to selection of stocks to portfolio, here are two main questions: it is useful to build sector synthetic measures of development in securities analyses? The second is how to use such sectors division in securities analysis? In the paper at first all securities was divided by sectors and in the next step for such groups were built synthetic measures of development. A classification of securities on sectors were used to construction of portfolio. The search was done for all listed companies on Warsaw Stock Exchange, which are noted on the capital market from 2000 year. In the research, especially in sector classification by using synthetic measures of development was used year's economic and financial ratios in period of 2000-2002 years.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (12); 2005; nr 1076, s. 210-219